2022
DOI: 10.1177/20552076221074482
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effectiveness of an e-health program versus a home rehabilitation program in patients with chronic low back pain: A double blind randomized controlled trial

Abstract: Objetive We conducted a randomized double blind clinical trial, to compare the effectiveness of McKenzie exercises and electroanalgesia via an e-Health program versus a home rehabilitation program on functionality, pain, fear of movement and quality of life in patients with non-specific chronic low back pain. Methods Seventy-four participants with non-specific chronic low back pain were randomized to either the e- Health program group (n = 39) or the home rehabilitation program group (n = 35). The intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
13

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 48 publications
0
17
0
13
Order By: Relevance
“…The participants were aged 18 years old or more, belonged to the age group from 18 to 65, or were 85 years old with unspecified upper limit. Some considered intermediate ages of 28 to 48 years old ( 15 ) , 30 to 55 ( 16 ) , and 30 to 67 ( 17 ) , and one study included participants aged over 55 years old ( 18 ) . The mean age in the intervention Group was 49.1 (SD: 7.4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The participants were aged 18 years old or more, belonged to the age group from 18 to 65, or were 85 years old with unspecified upper limit. Some considered intermediate ages of 28 to 48 years old ( 15 ) , 30 to 55 ( 16 ) , and 30 to 67 ( 17 ) , and one study included participants aged over 55 years old ( 18 ) . The mean age in the intervention Group was 49.1 (SD: 7.4).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the design of the studies, all of them were RCTs, published between 2002 and 2022 with predominance of 2019 with 6 (24%) ( 2 , 6 - 7 , 18 ; 19 - 20 ) and of 2021 with 4 (16%) ( 8 , 21 - 22 ) . Of the 25 studies, 9 (36%) were conducted in the United States of America ( 6 , 21 , 23 ; 24 ; 25 ; 26 ; 27 ; 28 - 29 ) , 5 (20%) in Australia ( 8 , 18 ; 19 ; 20 , 30 ) , 3 (12%) in Germany ( 2 , 14 , 31 ) , 2 (8%) in Spain ( 17 )( 32 ) , and 1 (4%) each in several countries such as India ( 33 ) , Netherlands ( 7 ) , Iran ( 15 ) , Jordan ( 16 ) , Italy ( 34 ) , Denmark and Norway ( 22 ) . The overall total was 5,142 participants, varying from 30 to 779 subjects in each study; 9 (36%) studies had sample sizes smaller than 100 participants ( 2 , 14 ; 15 ; 16 ; 17 ; 18 - 19 , 30 , 33 ) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 26 Recently published studies have demonstrated the efficacy of eHealth interventions in managing pain and improving functional status in other chronic pain conditions, such as chronic low back pain. 27 28 Furthermore, a digital-based cognitive–behavioural intervention for insomnia has shown promising results to improve depressive and anxiety symptoms in patients with insomnia. 29 …”
Section: Introductionmentioning
confidence: 99%
“…In addition, eHealth therapeutic education sessions may be held synchronously where both the patient and healthcare provider engage in real-time interaction and asynchronously as a tool for the subject’s self-management 26. Recently published studies have demonstrated the efficacy of eHealth interventions in managing pain and improving functional status in other chronic pain conditions, such as chronic low back pain 27 28. Furthermore, a digital-based cognitive–behavioural intervention for insomnia has shown promising results to improve depressive and anxiety symptoms in patients with insomnia 29…”
Section: Introductionmentioning
confidence: 99%